Assembly of Highly Functionalized Allylic Sulfones via a Stereoselective Pd‐Catalyzed Sequential C−C/C−S Cleavage and C−S Formation Process. Issue 19 (17th May 2021) - Zhang, Ning; Miao, Lingling; Yang, Yu; Duan, Guohang; Shi, Linlin; Hao, Xin‐Qi; Song, Mao‐Ping; Xu, Yan; Zhu, Xinju
Abstract: A Pd‐catalyzed sequential C−C/C−S cleavage and C−S formation approach for highly functionalized allylic sulfones synthesis of vinylcyclopropanes with p ‐tosylmethyl isocyanide has been developed under mild conditions. Importantly, the reaction of modular VCPs and TosMIC would give access to ( E )‐allylic sulfones in a stereoselective and regioselective fashion onto the in situ formed Pd intermediate. The current protocol featured broad substrate scope, operational convenience, and gram‐scale production. Abstract : An efficient Pd(0)‐catalyzed sulfonylation was carried out by using electron withdrawing groups substituted vinylcyclopropanes as allylating reagent and TosMIC as sulfonylating reagent under air. Allylic sulfones was synthesized in good yield and high regioselectivity via a sequential C−C bond and C−S bond cleavage and a new C−S bond formation process onto the in situ formed Pd intermediate. The current protocol featured operational convenience, gram‐scale production and broad substrate scope with the highest yield reaching 89 %, E / Z >99 : 1.